Premenstrual Syndrome and Premenstrual Dysphoric Disorder in Medical and Nursing Students of a Tertiary Care Teaching Hospital in Nepal - Aryal, Shreyashi; Thapa, Babita; Pant, Sagun Ballav (Nepal Journal of Obstetrics and Gynaecology, 2018)
Aims: To determine the prevalence of premenstrual syndrome and premenstrual dysphoric disorder and their association with psychiatric cases and dysmenorrhea in students of Lumbini Medical College, Palpa, Nepal. Methods: This is a cross-sectional study where self-report questionnaires based on American College of Obstetrics and Gynecology and Diagnostic and Statistical Manual of Mental Disorders-V criteria for PMS and PMDD and the General Health Questionnaire-12 for psychiatric caseness were filled by the students. The results were calculated using SPSS 16.0 as frequencies, mean, standard deviation and chi square with a p-value of < 0.05 as significant. Results: There were 382 participants out of which 113 (61.1%) medical and 126 (64%) nursing students met the ACOG criteria for PMS. PMDD was diagnosed in 78 (39.6%) nursing students and 72(38.9%) medical students. The most common somatic symptom was headache 256(77%) and behavioral symptom was irritability 310(81.2%). A significant relation (p value <0.05) was seen between psychiatric caseness, dysmenorrhoea and PMS/PMDD. Conclusion: PMS and PMDD are common in young medical and nursing students. A significant relation was present between PMS and psychiatric caseness and dysmenorrhea therefore comprehensive efforts should be made by healthcare providers to screen and manage symptoms including dysmenorrhea efficiently, thereby improving daily functioning, academic performance and professional skills of the students.